Pengaruh Akupresur Terhadap Pengurangan Mual Muntah Pada Ibu Hamil Trimester I di BPM Afah Fahmi A.Md Keb Surabaya - Meiri, Eka; Sartika, Wiwik (Infokes, 2018)
The complaints felt by the first trimester pregnant women are nausea vomiting (emesis gravidarum). Nausea and vomiting in pregnant women is a common occurrence, especially in the trimester I. In some pregnant women, nausea and vomiting that occur in the trimester I may continue until delivery. Severe nausea and vomiting, called hyperemesis gravidarum, can be harmful to the mother and fetus, because of the difficult nutrients to enter. The purpose of this study was to determine whether there is an effect of acupressure on reducing nausea of ​​vomiting in trimester pregnant women at BPM Afah Fahmi, Amd. Keb Surabaya. Sampling technique in this research is Purposive sampling. Using One group pretest - Postest design. The population in this study were all the trimester I pregnant women who experienced nausea vomiting while the study sample of 15 respondents. The instrument used is an observation sheet. The technique used to determine the effect of dependent and independent variables is the Wilcoxon Statistics test. The results of research conducted in BPM Afah Fahmi, Amd.Keb Surabaya is the trimester I pregnant women who experienced nausea vomiting after given acupressure decreased nausea vomiting. From Wilcoxon test results obtained p-value 0.000 <α (0.05).The conclusion in this research is there is effect of giving acupressure to the reduction of nausea vomiting in pregnant woman of trimester I at BPM Afah Fahmi, Amd Keb Surabaya. Therefore, pregnant women who experience nausea, vomiting is recommended to perform acupressure on health professionals because it is easier and more effective.